Vocabulary Size and Usage: Enriching Lexicon Via Reader Response - Nadarajan, Shanthi (1999)

(untitled)
Effective use of appropriate vocabulary has always been associated with mastery of a language but little attention is given to vocabulary building in the ESL classroom. A six week study based on a combined experiment on reading and interactive vocabulary instruction conducted amongst eighty advanced Malaysian fifth formers from four schools, tested the hypothesis that L2 students exposed to a combination of regular periods of reading and interactive vocabulary instruction of stylistics and canonical literary text would show significant increase in their ability to respond to literary text. The students' lexical richness and lexical frequency profile was measured via a computer software known as Vocabprofile. The results of the study showed that it was possible to obtain a reliable measure of lexical richness, which was stable across a cross section of L2 students. It was established that ESL speakers could increase their lexical richness with additional assistance from other sources within a specified period. However, their lexical variation does not increase at a similar pace or match the level of native speakers' writings.